2020
DOI: 10.1093/nar/gkaa049
|View full text |Cite
|
Sign up to set email alerts
|

FAM46B is a prokaryotic-like cytoplasmic poly(A) polymerase essential in human embryonic stem cells

Abstract: Family with sequence similarity (FAM46) proteins are newly identified metazoan-specific poly(A) polymerases (PAPs). Although predicted as Gld-2-like eukaryotic non-canonical PAPs, the detailed architecture of FAM46 proteins is still unclear. Exact biological functions for most of FAM46 proteins also remain largely unknown. Here, we report the first crystal structure of a FAM46 protein, FAM46B. FAM46B is composed of a prominently larger N-terminal catalytic domain as compared to known eukaryotic PAPs, and a C-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 65 publications
4
29
0
Order By: Relevance
“…We next investigated the preference of rnGLD-2 for nucleotides and substrate RNAs. The consumption of ATP/GTP/UTP/CTP in the presence of A 15 oligo substrate was individually monitored in time course based on an HPLC-based quantification assay ( 47 ). After 12 min, around 75% ATP and 40% GTP was consumed by rnGLD-2, whereas over 90% UTP and CTP remained unhydrolyzed, suggesting that rnGLD-2 prefers ATP over other nucleotides during polyadenylation (Figure 5A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We next investigated the preference of rnGLD-2 for nucleotides and substrate RNAs. The consumption of ATP/GTP/UTP/CTP in the presence of A 15 oligo substrate was individually monitored in time course based on an HPLC-based quantification assay ( 47 ). After 12 min, around 75% ATP and 40% GTP was consumed by rnGLD-2, whereas over 90% UTP and CTP remained unhydrolyzed, suggesting that rnGLD-2 prefers ATP over other nucleotides during polyadenylation (Figure 5A ).…”
Section: Resultsmentioning
confidence: 99%
“…While cytoplasmic polyadenylation in mammalian development is a pivotal event, it is possible that other PAPs take over or share this responsibility in mammals. For example, members of FAM46 proteins, recently reported as active non-canonical PAPs ( 47 , 56 ), showed specifically increased expression during gametogenesis and early embryonic development. The fact that mammalian GLD-2s are intrinsically potent PAPs and stay in a constitutive active state suggests that they may not need GLD-3- or RNP-8-like partners as in C. elegans to stimulate PAP activity.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, human TENT5B has almost exclusive preference for ATP incorporation, suggesting that TENT5 proteins are highly unlikely to perform mixed RNA tailing. Biochemical analysis revealed that human TENT5B prefers substrate RNAs that are adenosine‐rich close to the very 3′ end, suggesting that TENT5 proteins preferentially act on already polyadenylated mRNAs (Hu et al, 2020). The functional relevance of cytoplasmic polyadenylation by TENT5 ncPAP is only beginning to emerge because it is a relatively newly discovered family of TENTs (Figure 4) (Kuchta et al, 2016).…”
Section: Noncanonical Polyadenylationmentioning
confidence: 99%
“…As mentioned above, the structure of xtTENT5B protein has been solved, and the biochemical properties of TENT5B have recently been reported (Hu et al, 2020). However, few studies have described the functional relevance of this ncPAP.…”
Section: Noncanonical Polyadenylationmentioning
confidence: 99%
See 1 more Smart Citation